PROTOTYPE WEATHER STATION BERBASIS ARDUINO YUN - Asep Saefullah; Abas Sunarya; Deinsyah Fakhrizal (CCIT Journal, 2015)
A weather monitoring station that is simple and able to take the data of weather conditions parameters can be used to determine the local weather conditions at a point place. The process of data transmission between monitoring station weather conditions can be done by utilizing a wireless communication (wireless) network or the Internet. using DHT11 sensor, BMP180 and LDR to measure weather parameters, among which temperature, humidity, light intensity, air pressure and altitude. With Prototype research methods can provide ideas for the maker and potential users on how the system will function in full shape. The concept of Embedded Systems is growing very rapidly with the number of devices that carry the concept. Embedded System is a computer system with a specific purpose, which is entirely incorporated into the device you want to control. One development tool that brings this concept is Arduino Yun. Arduino that has been equipped with an Atheros AR9331 support for troubleshooting Ethernet networks. In Atheros AR9331 processor has been equipped with Linino OS (based on OpenWRT Linux) to assist in data communications in WiFi or Wire. Embedded systems Yun Arduino microcontroller can be connected with a local WiFi network. With its ability Arduino Yun can send output to the internet via social networks like Facebook. Through Temboo can easily send outputs on Facebook, using Facebook Library which had been prepared by a special Temboo for Arduino Yun and APIs (Application Programming Interfaces). The result is a prototype weather station that can be viewed directly on Facebook as a status within one hour.